New Gen New System (NGNS) sebagai Upaya Pengembangan Kepribadian dan Sistem Pembelajaran Siswa - Shabira, Adila; Zaqiyatunnisa, Ayda; Aini, Qurrotu; Chasanah, Richa Nur; Firdausyi, Roudhotul; Budi, Sevilla Andina; Alevia, Shelva Dian; Santi, Dwi Rukma (ABDIMASY: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2024)
Students' personality can be influenced by the school environment, especially through learning interactions and a conducive classroom atmosphere. The purpose of this service is to develop students' personalities and learning systems at MINU Tambak Sumur, Sidoarjo, East Java, using the Community-Based Research (CBR) method and Cognitive-Behavioral Therapy (CBT) techniques, rewards, and development of learning processes and aspects. The results showed positive developments in student attitudes and improvements in the learning process, although these were not permanent in the classroom and participants were not fully compliant with the techniques provided. Reinforcement of behavior and adherence is essential to sustain such progress.